Mock Trial: The Cold War Human Radiation Experiments - Lee, Matthew (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
Instructions for class mock trial on The Cold War Human Radiation Experiments Truth and Reconciliation Commission